Bat STING drives IFN-beta production in anti-RNA virus innate immune response - Fu, Feiyu; Shao, Qi; Zhang, Jianjian; Wang, Jie; Wang, Zhaofei; Ma, Jingjiao; Yan, Yaxian; Sun, Jianhe; Cheng, Yuqiang (Frontiers in Microbiology, 2023)
The ability of stimulator of interferon genes (STING) to activate interferon (IFN) responses during RNA virus infection has been demonstrated in different mammalian cells. Despite being the host of numerous RNA viruses, the role of STING in bats during RNA virus infection has not been elucidated. In this study, we identified and cloned the STING gene of the Brazilian free-tailed bat Tadarida brasiliensis (T. brasiliensis). The full-length bat STING (BatSTING) encodes 376 amino acids, with the highest similarity to cattle STING. Using Green fluorescent protein (GFP) tagged vesicular stomatitis virus (VSV) VSV-GFP as a model, we determined that overexpression of STING in T. brasiliensis 1 lung (TB1 Lu) cells stimulated by cGAS significantly inhibited RNA virus replication, and the antiviral activities were associated with its ability to regulate basal expression of IFN-β and some IFN stimulated genes (ISGs). In addition, we found that BatSTING was able to be activated after stimulation by diverse RNA viruses. The results of TB1 Lu cells with STING deficiency showed that knockdown of BatSTING severely hindered the IFN-β response triggered by VSV-GFP. Based on this, we confirm that BatSTING is required to induce IFN-β expression during RNA virus infection. In conclusion, our experimental data clearly show that STING in bat hosts plays an irreplaceable role in mediating IFN-β responses and anti-RNA virus infection.